Design And Development Of Polarimetric FM-CW Imaging Radar - Yang, Oliver Ang Chin (2010)
This thesis deal with the ground-based fully polarimetric system of its design and construction arrangement. The asserted system is conducted for short range operation and adequately determines the complete polarimetric images of various natural targets. The system will be operated using Frequency Modulated Continuous Wave (FM-CW) technique. With this technique, it induces elementary characteristics for short range radar and more cost effective hardware design which minimize development time, cost and complexity. With that, the proposed system will be constructed using connectorized off the shelf Radio Frequency (RF) components.